Climate alpha and the global capital market - Alexander Golub; Jon Anda; Anil Markandya; Michael Brody; Aldin Celovic; Angele Kedaitiene (Fondazione Eni Enrico Mattei (FEEM), 2022)
The way in which climate policy and climate risks are currently accounted for in financial and real investment decisions is inadequate. The paper demonstrates weaknesses in methods presently used and proposes an alternative that aims to bridge the duration gap between climate policy modeling and mitigation capital. The core tool is real options analysis combined with an Integrated Assessment Framework designed to capture the complex set of issues linking climate change, climate policy and the economy. The tools are meant for use in both capex decisions by corporations and portfolio decisions by investors. The tools will be a hedge against the risk of mitigation short squeeze occurring because investment is deferred beyond the 5 year or less timeframe of finance.
Keywords: G11; G17; G18; Q54; 330; Climate alpha; option value; abatement short squeeze; green transition